Polyimide-polyurethane copolymer modified epoxy resin adhesive and preparation method thereof
By modifying the epoxy resin adhesive with polyimide-polyurethane copolymer, an interpenetrating network IPN structure is formed, which solves the brittleness, heat resistance and adhesive properties of the epoxy resin adhesive in humid and hot environments, and achieves better mechanical and heat resistance.
Patent Information
- Application Number
- CN202510062929.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-15
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2045-01-15
AI Technical Summary
The existing epoxy resin adhesives have brittle texture, poor heat resistance and poor adhesive properties after cross-linking and curing in humid and hot environments.
Using polyimide-polyurethane copolymer modified epoxy resin adhesive, by copolymerizing the polyamic acid prepolymer and the polyurethane prepolymer, polyurethane of polyimide blocks is obtained, and physically crosslinked with the epoxy resin to form an interpenetrating network IPN structure.
The toughness, heat resistance and bonding properties of epoxy resin are improved, especially in the conditions of humid and heat and high-temperature boiling.
Smart Images

Figure CN119859496A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a copolymer modified epoxy resin adhesive and a preparation method thereof. Background Art
[0002] In a hot and humid environment, the adhesive will undergo physical changes such as expansion and softening, and the mechanical properties and initial thermal decomposition temperature of the adhesive will gradually decrease, and the bonding performance will be reduced. Hot and humid conditions will trigger chemical reactions inside the adhesive, such as hydrolysis and oxidation, which will destroy the molecular structure of the adhesive. The aging of epoxy resin in a hot and humid environment may be due to the degradation of chain segments at the CN bonds in the main chain, oxidation reactions at hydroxyl groups and methylene groups connected to nitrogen atoms, etc. Boiling and hot and humid conditions may also cause interface damage between the adhesive and the adherend, seriously affecting the bonding strength and mechanical properties.
[0003] The research on adhesives under hot and humid conditions mainly focuses on their aging behavior and environmental damage mechanisms. Studies have shown that the performance of adhesives will be significantly affected under hot and humid conditions, especially the shear strength and initial thermal decomposition temperature. As aging continues, these performance indicators will gradually decrease.
[0004] Moisture-resistant adhesives show good performance in high temperature and high humidity environments. This adhesive has self-leveling properties, and after curing, the surface is smooth, bright, and free of bubbles. In addition to having good waterproof properties, its sealing performance is also very good. However, moisture-resistant adhesives also have some limitations.
[0005] Although moisture-resistant adhesives perform well in high-temperature and high-humidity environments, their performance may be affected under extreme moisture and heat conditions. For example, the adhesive bond strength may decrease or the adhesive itself may degrade or deform after prolonged exposure to extremely high temperatures and humidity.
[0006] Since moisture-heat resistant adhesives need to have special properties, their production costs may be high. This may limit their use in some cost-sensitive applications. In order to achieve good moisture-heat resistance, the preparation process of moisture-heat resistant adhesives may be more complicated. This may increase the difficulty of control during the production process, thereby affecting the quality stability of the product.
[0007] Epoxy resin has good comprehensive mechanical properties, strong adhesion, small shrinkage, good stability, and excellent electrical insulation properties. It has been widely used in the fields of machinery, electronics, electrical appliances, aerospace, aviation, and coating bonding as coatings, adhesives, composite resin matrices, and electronic packaging materials. However, due to the high cross-linking density of cured epoxy resin, it is brittle, and has poor toughness and impact resistance. Therefore, toughening and modification of epoxy resin has always been a hot topic for researchers at home and abroad.
[0008] Regardless of the material used to toughen epoxy resin, it can be divided into three types: chemical toughening method (the toughening agent and epoxy resin undergo chemical crosslinking), physical toughening method (the toughening agent and epoxy resin do not undergo chemical crosslinking) and chemical-physical synergistic method.
[0009] The molecular chain of polyurethane contains a large number of ether bonds or ester bonds, which have a low internal rotation barrier, and the molecular chain segments are easy to rotate and show good flexibility. Therefore, using polyurethane to modify it can effectively improve the flexibility of epoxy resin. Epoxy resin can be blended with polyurethane to form a copolymer with cross-linking and interpenetrating networks.
[0010] However, polyurethane materials have poor heat resistance. The operating temperature range of polyurethane materials is -40 to 120°C. When the temperature exceeds 100°C, it is easy to soften and deform, resulting in a significant decrease in the mechanical properties of the material. Especially for polyurethane materials with only physical crosslinking, the long-term operating temperature cannot exceed 80°C, which limits the application range of polyurethane modified epoxy resin at high temperatures to a certain extent.
[0011] Polyimide (PI) is an aromatic rigid nitrogen-containing heterocyclic polymer with excellent heat resistance and mechanical properties. As a functional material, polyimide (PI) is the polymer material with the highest heat resistance level used in the industrial field so far. Because of its excellent mechanical properties and good heat resistance, electrical properties and mechanical strength, it plays an important role in aerospace, electrical appliances, communications and other industries. Introducing polyimide into the main chain of polyurethane can improve the heat resistance of the copolymer.
[0012] At present, physical blending and chemical modification are mainly used for the modification of polyurethane and polyimide. Blending modification is to modify polyurethane materials by forming an alloy with polyimide and polyurethane. However, due to the shortcomings of polyimide being insoluble and infusible and having poor processability, the soft segments of the alloy formed by polyurethane and polyimide with different molecular weights are phase separated, and the alloy has a three-phase structure. The subsequent application effect of the products modified by this method is not good. Summary of the invention
[0013] The present invention aims to solve the problems of brittle texture, poor heat resistance and poor bonding performance under hot and humid conditions of the existing epoxy resin adhesive after cross-linking and curing, and further provide a polyimide-polyurethane copolymer modified epoxy resin adhesive and a preparation method thereof.
[0014] A polyimide-polyurethane copolymer modified epoxy resin adhesive is prepared from a polyamic acid prepolymer, a polyurethane prepolymer and an epoxy resin. Specifically, the polyamic acid prepolymer is added to a polyurethane prepolymer for copolymerization to obtain a polyamic acid-blocked polyurethane prepolymer, the polyamic acid-blocked polyurethane prepolymer is thermally imidized to obtain a polyimide-blocked polyurethane, and finally the polyimide-blocked polyurethane is added to an epoxy resin for physical crosslinking; the molar ratio of the polyurethane prepolymer to the polyamic acid prepolymer is (2.01-3):1; the mass ratio of the polyimide-blocked polyurethane to the epoxy resin is (0.1-0.4):1;
[0015] The polyamic acid prepolymer is synthesized from aromatic diamine and aromatic dianhydride; the aromatic diamine is m-phenylenediamine; the aromatic dianhydride is 3,3',4,4'-biphenyltetracarboxylic dianhydride, 4,4'-(hexafluoroisopropylene) diphthalic anhydride, 4,4'-biphenyl ether dianhydride or 3,3',4,4'-dibenzophenone tetracarboxylic dianhydride;
[0016] The polyurethane prepolymer is synthesized from dehydrated polyol and dehydrated isocyanate; the dehydrated isocyanate is toluene-2,4-diisocyanate; the dehydrated polyol is polybutylene glycol;
[0017] The general structural formula of the polyimide-blocked polyurethane is:
[0018] Where n = 5 to 7;
[0019] The R1 is
[0020] The R2 is Wherein m=5~13.
[0021] A method for preparing a polyimide-polyurethane copolymer modified epoxy resin adhesive is carried out according to the following steps:
[0022] 1. Preparation of polyamic acid prepolymer:
[0023] Weigh aromatic diamine, aromatic dianhydride and organic solvent in proportion, add aromatic diamine to organic solvent and stir to dissolve at room temperature, then add aromatic dianhydride and stir to dissolve at room temperature, then react for 1h to 2h at 20°C to 40°C, add deionized water under high-speed stirring after the reaction, stop stirring when the system becomes a milky white suspension, filter and wash, and finally dry to obtain a polyamic acid prepolymer;
[0024] 2. Preparation of polyurethane prepolymer:
[0025] Dehydrating the isocyanate and the polyol respectively, then weighing the dehydrated polyol and the dehydrated isocyanate in proportion, and then dripping the dehydrated isocyanate into the dehydrated polyol under a nitrogen atmosphere at a temperature of 60° C. to 80° C. for reaction for 2 h to 3 h to obtain a polyurethane prepolymer;
[0026] 3. Preparation of polyurethane prepolymer with polyamic acid block:
[0027] Under the conditions of nitrogen atmosphere and temperature of 60° C. to 80° C., adding polyamic acid prepolymer to polyurethane prepolymer for reaction for 0.5 h to 1 h to obtain polyamic acid-blocked polyurethane prepolymer;
[0028] The molar ratio of the polyurethane prepolymer to the polyamic acid prepolymer is (2.01-3):1;
[0029] 4. Thermal imidization:
[0030] In a nitrogen atmosphere, the polyurethane prepolymer with polyamic acid blocks is thermally imidized to obtain a polyurethane with polyimide blocks;
[0031] 5. Blending of polyimide-blocked polyurethane and epoxy resin:
[0032] Under the conditions of nitrogen atmosphere and temperature of 60°C to 80°C, adding polyimide-blocked polyurethane to epoxy resin for reaction for 1h to 3h to obtain polyimide-polyurethane copolymer-modified epoxy resin adhesive;
[0033] The mass ratio of the polyurethane of the polyimide block to the epoxy resin is (0.1-0.4):1.
[0034] The beneficial effects of the present invention are:
[0035] The invention provides a polyimide-polyurethane copolymer modified epoxy resin adhesive, which is different from the traditional polyurethane modified epoxy resin. While enhancing the toughness of the epoxy resin, the introduction of the imide group also improves the heat resistance and bonding performance of the system.
[0036] The present invention adopts a copolymer modified epoxy resin adhesive-polyimide-blocked polyurethane polymer, and the copolymer and epoxy resin penetrate each other to form an interpenetrating network IPN structure. The IPN structure can disperse tensile stress. When subjected to external tensile stress, the tensile force will be transmitted from one network to another, the molecular structure is not easy to be destroyed, and the toughness of the system is improved. The modified epoxy polyimide polyurethane polymer is divided into a hard segment structure and a soft segment structure. The hard segment is mainly a PI molecular chain structure, and the soft segment is mainly a flexible segment of PU. The PI segment has a high-strength rigid structure and becomes the overall skeleton structure of the IPN system. The imide ring and the aromatic ring in the molecular chain have a conjugated effect, the electron cloud distribution in the conjugated system is relatively uniform, the internal energy of the molecule is low, and the molecular structure is not easily destroyed. The conjugated effect also enhances the rigidity and modulus of the system, so that the system has a good supporting effect. The main chain of the PI molecule carries a benzene ring structure and an imide ring structure, which increases the polarity and hydrogen bonding degree between the hard segments, increases the hard segment force, and hinders the movement of the molecular chain. The imide group is also a polar group, which can react with the polar hydroxyl and epoxy groups in the epoxy resin to form chemical bonds, increasing the cohesive energy density of the system. The molecular chain is difficult to move, and the cohesive energy density of the system increases, which increases the modulus of the system and enhances the mechanical properties and heat resistance. PU, as a soft segment, can undergo microphase separation with the hard segment and form a co-continuous phase or a particle dispersed phase with the epoxy resin, thereby increasing the toughness of the epoxy resin and improving its mechanical properties. The polyimide block polyurethane copolymer modified epoxy resin not only improves the temperature resistance of the system, but also improves the mechanical properties of the system, so the adhesive has good high-temperature bonding properties.
[0037] When the adhesive is immersed in water, the support of the rigid structure prevents the system from absorbing water and expanding; when in a high temperature environment, the system will not shrink due to heat, so the adhesive is resistant to high temperature boiling. Although the hard segment of the PI molecular chain segment has rigidity and heat resistance, and serves as a scaffold to support the skeleton of the material, the pure PI structure is easily penetrated by water molecules in a humid environment, and the mechanical properties are reduced. The PU structure, which is the flexible segment in the IPN structure, contains a large number of flexible groups, among which the ether bond has low cohesive energy, is easy to rotate, and the molecular chain segment is easy to move, which can fill the gaps in the system. In addition to playing a toughening role, the flexible PU segment also prevents water molecules from penetrating into the system, reduces the water absorption rate, and maintains good bonding performance when the material is in boiling and wet heat conditions. The modified polyimide-polyurethane block copolymer has a more complex segment, increased steric hindrance, and more difficult for water molecules to penetrate, and a lower water absorption rate, so that the adhesive can maintain good bonding performance under boiling and wet heat conditions. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] Figure 1 This is the FTIR spectrum of the polyimide-segmented polyurethane prepared in step 4 of Example 1. DETAILED DESCRIPTION
[0039] Specific implementation method 1: A polyimide-polyurethane copolymer modified epoxy resin adhesive of this implementation method is prepared from polyamic acid prepolymer, polyurethane prepolymer and epoxy resin, specifically, polyamic acid prepolymer is added to polyurethane prepolymer for copolymerization to obtain polyamic acid segmented polyurethane prepolymer, polyamic acid segmented polyurethane prepolymer is thermally imidized to obtain polyimide segmented polyurethane, and finally polyimide segmented polyurethane is added to epoxy resin for physical crosslinking; the molar ratio of polyurethane prepolymer to polyamic acid prepolymer is (2.01-3):1; the mass ratio of polyimide segmented polyurethane to epoxy resin is (0.1-0.4):1;
[0040] The polyamic acid prepolymer is synthesized from aromatic diamine and aromatic dianhydride; the aromatic diamine is m-phenylenediamine; the aromatic dianhydride is 3,3',4,4'-biphenyltetracarboxylic dianhydride, 4,4'-(hexafluoroisopropylene) diphthalic anhydride, 4,4'-biphenyl ether dianhydride or 3,3',4,4'-dibenzophenone tetracarboxylic dianhydride;
[0041] The polyurethane prepolymer is synthesized from dehydrated polyol and dehydrated isocyanate; the dehydrated isocyanate is toluene-2,4-diisocyanate; the dehydrated polyol is polybutylene glycol;
[0042] The general structural formula of the polyimide-blocked polyurethane is:
[0043] Where n = 5 to 7;
[0044] The R1 is
[0045] The R2 is Wherein m=5~13.
[0046] This specific implementation method uses the prepolymer method. The first step is to synthesize oligomer polyamic acid, the second step is to synthesize -NCO-terminated PU prepolymer, and then the PU prepolymer and polyamic acid (precursor of polyimide) are used to block to prepare a polyurethaneimide copolymer. The resulting product has a ternary network structure.
[0047] Taking advantage of the good compatibility of polyimide precursor polyamic acid with polyurethane, polyamic acid was introduced into the polyurethane main chain by solution polymerization to synthesize linear polyamic acid-polyurethane block copolymers, which were then thermally imidized to prepare cross-linked polyimide-polyurethane block copolymers.
[0048] Compared with polyurethane, the imide-treated polyimide-polyurethane block copolymer is blended with epoxy resin. The toughness of epoxy resin is improved while the heat resistance is further improved. The modified adhesive can maintain its excellent bonding performance under wet heat and boiling conditions. The modified epoxy resin adhesive not only solves the problems of brittleness and heat resistance, improves toughness and heat resistance, but also improves water resistance and reduces water absorption. The imide ring in the system is a rigid structure and is not easy to expand when absorbing water. The polyurethane segment fills the gaps in the system, making it difficult for water molecules to penetrate. The epoxy resin adhesive modified by polyimide-polyurethane block copolymer is not easy to absorb water and expand under wet heat and boiling conditions, and can also maintain good bonding performance.
[0049] The beneficial effects of this specific implementation are:
[0050] This specific embodiment provides a polyimide-polyurethane copolymer modified epoxy resin adhesive, which is different from the traditional polyurethane modified epoxy resin. While enhancing the toughness of the epoxy resin, the introduction of the imide group also improves the heat resistance and bonding performance of the system.
[0051] This specific embodiment adopts a copolymer modified epoxy resin adhesive-polyimide-blocked polyurethane polymer, and the copolymer and epoxy resin penetrate each other to form an interpenetrating network IPN structure. The IPN structure can disperse tensile stress. When subjected to external tensile stress, the tensile force will be transmitted from one network to another, the molecular structure is not easy to be destroyed, and the toughness of the system is improved. The epoxy-modified polyimide polyurethane polymer is divided into a hard segment structure and a soft segment structure. The hard segment is mainly a PI molecular chain structure, and the soft segment is mainly a flexible segment of PU. The PI segment has a high-strength rigid structure and becomes the overall skeleton structure of the IPN system. The imide ring and the aromatic ring in the molecular chain have a conjugated effect, the electron cloud distribution in the conjugated system is relatively uniform, the internal energy of the molecule is low, and the molecular structure is not easily destroyed. The conjugation effect also enhances the rigidity and modulus of the system, so that the system has a good supporting effect. The main chain of the PI molecule carries a benzene ring structure and an imide ring structure, which increases the polarity and hydrogen bonding degree between the hard segments, increases the hard segment force, and hinders the movement of the molecular chain. The imide group is also a polar group, which can react with the polar hydroxyl and epoxy groups in the epoxy resin to form chemical bonds, increasing the cohesive energy density of the system. The molecular chain is difficult to move, and the cohesive energy density of the system increases, which increases the modulus of the system and enhances the mechanical properties and heat resistance. PU, as a soft segment, can undergo microphase separation with the hard segment and form a co-continuous phase or a particle dispersed phase with the epoxy resin, thereby increasing the toughness of the epoxy resin and improving its mechanical properties. The polyimide block polyurethane copolymer modified epoxy resin not only improves the temperature resistance of the system, but also improves the mechanical properties of the system, so the adhesive has good high-temperature bonding properties.
[0052] When the adhesive is immersed in water, the support of the rigid structure prevents the system from absorbing water and expanding; when in a high temperature environment, the system will not shrink due to heat, so the adhesive is resistant to high temperature boiling. Although the hard segment of the PI molecular chain segment has rigidity and heat resistance, and serves as a scaffold to support the skeleton of the material, the pure PI structure is easily penetrated by water molecules in a humid environment, and the mechanical properties are reduced. The PU structure, which is the flexible segment in the IPN structure, contains a large number of flexible groups, among which the ether bond has low cohesive energy, is easy to rotate, and the molecular chain segment is easy to move, which can fill the gaps in the system. In addition to playing a toughening role, the flexible PU segment also prevents water molecules from penetrating into the system, reduces the water absorption rate, and maintains good bonding performance when the material is in boiling and wet heat conditions. The modified polyimide-polyurethane block copolymer has a more complex segment, increased steric hindrance, and more difficult for water molecules to penetrate, and a lower water absorption rate, so that the adhesive can maintain good bonding performance under boiling and wet heat conditions.
[0053] Specific embodiment 2: This embodiment is different from the specific embodiment 1 in that the molar ratio of the aromatic diamine to the aromatic dianhydride is (1.01-2): 1. The rest is the same as the specific embodiment 1.
[0054] Specific embodiment 3: This embodiment is different from specific embodiment 1 or 2 in that the molar ratio of the dehydrated isocyanate to the dehydrated polyol is (1.01-3): 1. The rest is the same as specific embodiment 1 or 2.
[0055] Specific embodiment 4: This embodiment differs from specific embodiments 1 to 3 in that: the epoxy resin is E-51 epoxy resin; the molecular weight of the polybutylene glycol is 1000 g / mol to 3000 g / mol. Other aspects are the same as specific embodiments 1 to 3.
[0056] Specific embodiment 5: This embodiment is a method for preparing a polyimide-polyurethane copolymer modified epoxy resin adhesive, which is carried out according to the following steps:
[0057] 1. Preparation of polyamic acid prepolymer:
[0058] Weigh aromatic diamine, aromatic dianhydride and organic solvent in proportion, add aromatic diamine to organic solvent and stir to dissolve at room temperature, then add aromatic dianhydride and stir to dissolve at room temperature, then react for 1h to 2h at 20°C to 40°C, add deionized water under high-speed stirring after the reaction, stop stirring when the system becomes a milky white suspension, filter and wash, and finally dry to obtain a polyamic acid prepolymer;
[0059] 2. Preparation of polyurethane prepolymer:
[0060] Dehydrating the isocyanate and the polyol respectively, then weighing the dehydrated polyol and the dehydrated isocyanate in proportion, and then dripping the dehydrated isocyanate into the dehydrated polyol under a nitrogen atmosphere at a temperature of 60° C. to 80° C. for reaction for 2 h to 3 h to obtain a polyurethane prepolymer;
[0061] 3. Preparation of polyurethane prepolymer with polyamic acid block:
[0062] Under the conditions of nitrogen atmosphere and temperature of 60° C. to 80° C., adding polyamic acid prepolymer to polyurethane prepolymer for reaction for 0.5 h to 1 h to obtain polyamic acid-blocked polyurethane prepolymer;
[0063] The molar ratio of the polyurethane prepolymer to the polyamic acid prepolymer is (2.01-3):1;
[0064] 4. Thermal imidization:
[0065] In a nitrogen atmosphere, the polyurethane prepolymer with polyamic acid blocks is thermally imidized to obtain a polyurethane with polyimide blocks;
[0066] 5. Blending of polyimide-blocked polyurethane and epoxy resin:
[0067] Under the conditions of nitrogen atmosphere and temperature of 60°C to 80°C, adding polyimide-blocked polyurethane to epoxy resin for reaction for 1h to 3h to obtain polyimide-polyurethane copolymer-modified epoxy resin adhesive;
[0068] The mass ratio of the polyurethane of the polyimide block to the epoxy resin is (0.1-0.4):1.
[0069] Specific implementation method 6: This implementation method is different from specific implementation method 5 in that the organic solvent in step 1 is N,N-dimethylacetamide; the mass ratio of the total mass of the aromatic diamine and aromatic dianhydride in step 1 to the organic solvent is 1:(2-5). The rest is the same as specific implementation method 5.
[0070] Specific embodiment seven: This embodiment is different from specific embodiment five or one of six in that: in step one, at room temperature and a stirring speed of 200r / min~400r / min, an aromatic diamine is added to an organic solvent and stirred to dissolve, then at room temperature, a stirring speed of 200r / min~400r / min and an addition rate of 1mL / min~2mL / min, an aromatic dianhydride is added and stirred to dissolve, and then at a temperature of 20℃~40℃ and a stirring speed of 400r / min~600r / min, the reaction is carried out for 1h~2h to obtain a reaction system, and after the reaction, at a stirring speed of 1000r / min~1200r / min and an addition rate of 3mL / min~5mL / min, deionized water is added to the reaction system, and stirring is stopped when the system becomes a milky white suspension, and then suction filtration is performed to obtain a filter cake, and the filter cake is washed 2~4 times with acetone and deionized water, and finally dried; the volume ratio of the reaction system to deionized water is 1:(1.5~2.5). The rest is the same as the fifth or sixth specific implementation.
[0071] Specific embodiment 8: This embodiment differs from any one of specific embodiments 5 to 7 in that the dehydration in step 2 is carried out at a temperature of 100° C. to 110° C. for 2 to 3 hours. The rest is the same as specific embodiments 5 to 7.
[0072] Specific embodiment 9: This embodiment is different from Specific embodiments 5 to 8 in that: in step 2, under the conditions of nitrogen atmosphere, temperature of 60°C to 80°C, stirring speed of 400r / min to 600r / min and dropping speed of 0.25mL / min to 1mL / min, the dehydrated isocyanate is dripped into the dehydrated polyol for reaction for 2h to 3h. The rest is the same as Specific embodiments 5 to 8.
[0073] Specific embodiment ten: This embodiment differs from specific embodiments five to nine in that the thermal imidization described in step four is specifically carried out under a nitrogen atmosphere, first at a temperature of 60°C to 65°C for 1h to 1.5h, then at a temperature of 70°C to 80°C for 1h to 1.5h, then at a temperature of 85°C to 90°C for 1h to 1.5h, then at a temperature of 95°C to 100°C for 1h to 1.5h, and finally at a temperature of 110°C to 120°C for 1h to 1.5h. The rest is the same as specific embodiments five to nine.
[0074] The following examples are used to verify the beneficial effects of the present invention:
[0075] Embodiment 1:
[0076] A method for preparing a polyimide-polyurethane copolymer modified epoxy resin adhesive is carried out according to the following steps:
[0077] 1. Preparation of polyamic acid prepolymer:
[0078] Weigh aromatic diamine, aromatic dianhydride and organic solvent in proportion, add aromatic diamine to organic solvent and stir to dissolve at room temperature and stirring speed of 400 r / min, then add aromatic dianhydride and stir to dissolve at room temperature, stirring speed of 400 r / min and adding speed of 1.5 mL / min, then react for 2 h at temperature of 30° C. and stirring speed of 400 r / min to obtain a reaction system, after the reaction, add deionized water to the reaction system at stirring speed of 1200 r / min and adding speed of 4 mL / min, stop stirring when the system becomes a milky white suspension, then filter to obtain a filter cake, wash the filter cake with acetone and deionized water 3 times, finally vacuum dry at temperature of 60° C. for 6 h to obtain a polyamic acid prepolymer; the volume ratio of the reaction system to deionized water is 1:1.5;
[0079] The molar ratio of the aromatic diamine to the aromatic dianhydride is 2:1; the mass ratio of the total mass of the aromatic diamine and the aromatic dianhydride to the organic solvent is 1:3; the aromatic diamine is m-phenylenediamine; the aromatic dianhydride is 3,3',4,4'-biphenyltetracarboxylic dianhydride; the organic solvent is N,N-dimethylacetamide;
[0080] 2. Preparation of polyurethane prepolymer:
[0081] Dehydrating the isocyanate and the polyol respectively, then weighing the dehydrated polyol and the dehydrated isocyanate in proportion, and then dripping the dehydrated isocyanate into the dehydrated polyol under the conditions of nitrogen atmosphere, temperature of 70°C, stirring speed of 600 r / min and dropping speed of 0.5 mL / min to react for 2 hours to obtain a polyurethane prepolymer;
[0082] The molar ratio of the dehydrated isocyanate to the dehydrated polyol is 2:1; the dehydrated isocyanate is toluene-2,4-diisocyanate; the dehydrated polyol is polybutylene glycol; the molecular weight of the polybutylene glycol is 3000 g / mol;
[0083] 3. Preparation of polyurethane prepolymer with polyamic acid block:
[0084] Under the conditions of nitrogen atmosphere and temperature of 70° C., adding polyamic acid prepolymer to polyurethane prepolymer for reaction for 1 hour to obtain polyamic acid-blocked polyurethane prepolymer;
[0085] The molar ratio of the polyurethane prepolymer to the polyamic acid prepolymer is 2.2:1;
[0086] 4. Thermal imidization:
[0087] In a nitrogen atmosphere, the polyurethane prepolymer with polyamic acid blocks is thermally imidized to obtain a polyurethane with polyimide blocks;
[0088] The structural formula of the polyimide-blocked polyurethane is:
[0089]
[0090] n = 5 to 7;
[0091] The R1 is
[0092] The R2 is m = 5 to 13;
[0093] 5. Blending of polyimide-blocked polyurethane and epoxy resin:
[0094] Under nitrogen atmosphere and temperature of 80°C, polyimide-blocked polyurethane was added to epoxy resin for reaction for 2 hours to obtain epoxy resin adhesive modified by polyimide-polyurethane copolymer;
[0095] The mass ratio of the polyimide-blocked polyurethane to the epoxy resin is 0.3:1; the epoxy resin is E-51 epoxy resin;
[0096] The dehydration in step 2 is specifically performed at a temperature of 110° C. for 3 hours;
[0097] The thermal imidization described in step 4 is specifically carried out under a nitrogen atmosphere, first at a temperature of 60°C for 1 hour, then at a temperature of 80°C for 1 hour, then at a temperature of 90°C for 1 hour, then at a temperature of 100°C for 1 hour, and finally at a temperature of 110°C for 1 hour.
[0098] Example 2: This example is different from Example 1 in that the aromatic dianhydride used in step 1 is 4,4'-(hexafluoroisopropylene) diphthalic anhydride, and the R1 The rest is the same as that of the first embodiment.
[0099] Example 3: This example is different from Example 1 in that the aromatic dianhydride used in step 1 is 4,4'-biphenyl ether dianhydride, and R1 is The rest is the same as that of the first embodiment.
[0100] Example 4: This example is different from Example 1 in that the aromatic dianhydride used in step 1 is 3,3',4,4'-benzophenone tetracarboxylic dianhydride, and R1 is The rest is the same as that of the first embodiment.
[0101] Embodiment 5: This embodiment is different from Embodiment 1 in that the molar ratio of the aromatic diamine to the aromatic dianhydride in step 1 is 3:2. The rest is the same as Embodiment 1.
[0102] Embodiment 6: This embodiment is different from Embodiment 1 in that the molar ratio of the aromatic diamine to the aromatic dianhydride in step 1 is 5:4. The rest is the same as Embodiment 1.
[0103] Embodiment 7: This embodiment is different from Embodiment 1 in that the molar ratio of the aromatic diamine to the aromatic dianhydride in step 1 is 6:5. The rest is the same as Embodiment 1.
[0104] Embodiment 8: This embodiment is different from Embodiment 1 in that the molar ratio of the aromatic diamine to the aromatic dianhydride in step 1 is 4:3. The rest is the same as Embodiment 1.
[0105] Embodiment 9: This embodiment is different from Embodiment 1 in that the synthesis temperature of isocyanate and polybutylene glycol in step 2 is 60° C. The rest is the same as Embodiment 1.
[0106] Embodiment 10: This embodiment is different from Embodiment 1 in that the synthesis temperature of isocyanate and polybutylene glycol in step 2 is 80° C. The rest is the same as Embodiment 1.
[0107] Comparative Example 1: This comparative example is different from Example 1 in that epoxy resin is used as an adhesive, and the addition of other substances and the preparation process are omitted; the epoxy resin structural formula is:
[0108] n=0.49~0.51. Others are the same as those in the first embodiment.
[0109] Comparative Example 2: This comparative example is different from Example 1 in that steps 1, 3 and 4 are omitted; the structural formula of the polyurethane prepolymer prepared in step 2 is:
[0110] n=13-15; in step 5, under nitrogen atmosphere and temperature of 80°C, the polyurethane prepolymer is added to the epoxy resin for reaction for 2 hours; the mass ratio of the polyurethane prepolymer to the epoxy resin is 0.3:1. The rest is the same as in Example 1.
[0111] Comparative Example 3: This comparative example is different from Example 1 in that: Steps 2 and 3 are omitted; in Step 1, aromatic diamine, aromatic dianhydride and organic solvent are weighed in proportion, and aromatic diamine is added to the organic solvent under the conditions of room temperature and stirring speed of 400r / min, and stirred to dissolve, and then aromatic dianhydride is added under the conditions of room temperature, stirring speed of 400r / min and adding speed of 1.5mL / min, and stirred to dissolve, and then reacted for 2h under the conditions of temperature of 30°C and stirring speed of 400r / min to obtain a polyamic acid prepolymer solution; in Step 4, the polyamic acid prepolymer solution is thermally imidized under a nitrogen atmosphere to obtain a polyimide; the structural formula of the polyimide is:
[0112] The R1 is n = 5 to 7;
[0113] In step 5, under the conditions of nitrogen atmosphere and temperature of 80° C., polyimide is added to epoxy resin for reaction for 2 hours; the mass ratio of polyimide to epoxy resin is 0.3:1. Other steps are the same as those in embodiment 1.
[0114] The materials and process parameters of Examples 1 to 10 and the comparative example are shown in Table 1:
[0115] Table 1
[0116]
[0117]
[0118]
[0119] Performance Testing:
[0120] 1. GPC: The relative molecular mass and relative molecular mass distribution were analyzed by LC-20AD gel chromatography of Shimadzu Corporation of Japan, using N,N-dimethylformyl (DMF) as the mobile phase of the chromatographic column and DMF as the solvent for the sample.
[0121] 2. Shear: The epoxy resin adhesive modified by polyimide-polyurethane copolymer and dicyandiamide curing agent (hereinafter referred to as dicyandiamide curing agent, Guangzhou Xinxi Metallurgical Chemical Co., Ltd., product model: SH-500) were mixed at a mass ratio of 100:10, and then applied to the bonding surfaces of two aluminum alloy specimens (6061-T6) and laminated, and then heated at a temperature of 110°C for 1 hour, and then heated at a temperature of 180°C for 1 hour to obtain a bonded part; the shear strength was tested using an Instron 5969 universal testing machine (US INSTRON Company). The room temperature shear strength was measured according to GB / T 7124-2008 standard; the 150°C shear strength was measured according to GJB444-1988 standard.
[0122] 3. Peeling: The 90° peeling strength was tested according to GJB 446-1988 standard. After the polyimide-polyurethane block copolymer modified epoxy was cured (mixed with dicyandiamide curing agent at a mass ratio of 100:10, then heated at 110°C for 1h and then heated at 180°C for 1h), the peeling strength was tested using Instron 5969 universal testing machine (INSTRON, USA).
[0123] 4. Impact: After the polyimide-polyurethane block copolymer modified epoxy was cured (mixed with dicyandiamide curing agent at a mass ratio of 100:10, then heated at 110°C for 1h and then heated at 180°C for 1h), the impact strength test was carried out on a pendulum impact testing machine in accordance with the national standard GB / T6328-1999 "Adhesive Shear Impact Strength Test Method".
[0124] 5. Rheological test: The viscosity-temperature curve of the sample is measured by a rheometer, the temperature range is from room temperature to 120°C, and the test speed is 10rad / s. The table data is the complex viscosity at 120°C.
[0125] 6. 5% thermal weight loss temperature (T 5% ): After curing (mixed with dicyandiamide curing agent at a mass ratio of 100:10, then heated at 110℃ for 1h and then at 180℃ for 1h), the polyimide-polyurethane block copolymer modified epoxy was subjected to a thermal gravimetric analyzer; the test was conducted using a thermal gravimetric analyzer (TGA), Q50 model from TA Instruments, USA. Heating rate: 10℃ / min, test atmosphere: air.
[0126] 7. DMA test: After curing (mixed with dicyandiamide curing agent at a mass ratio of 100:10, then heated at 110℃ for 1h, and then heated at 180℃ for 1h), the polyimide-polyurethane block copolymer modified epoxy was subjected to dynamic mechanical testing; then the dynamic mechanical testing was carried out using the DMAQ800 dynamic mechanical analyzer of TA Company of the United States. The sample size is (20~40)mm×(5~10)mm×(1~2)mm(length×width×height), the driving frequency is 1Hz, the heating rate is 5℃ / min, and the test temperature range is room temperature to 300℃.
[0127] 8. Water absorption test: After curing, the polyimide-polyurethane block copolymer modified epoxy was tested for water absorption (mixed with dicyandiamide curing agent at a mass ratio of 100:10, then heated at 110°C for 1h, and then heated at 180°C for 1h); at room temperature, the sample with a mass of m1 was completely immersed in deionized water for 24h, then the sample after water absorption was taken out and its surface moisture was wiped dry, and the sample mass was weighed and recorded as m3. The water absorption W is calculated according to the following formula:
[0128]
[0129] 9. Moisture heat treatment: According to the standard GB / T 30779-2014, the adhesive parts in test 2 are placed in a HS-50 constant temperature and humidity chamber for moisture heat treatment. First, the sample joint is placed at a relative humidity of 50% and a temperature of 23°C for 48 hours, and then the sample joint is placed in a constant temperature and humidity chamber at a relative humidity of 85% and a temperature of 85°C for moisture heat treatment for 24 hours, and finally placed at a relative humidity of 50% and a temperature of 23°C for 24 hours, and then a shear test is performed according to the GB / T 7124-2008 standard, and a DMA test is performed.
[0130] 10. Boiling cycle wet strength test: Place the adhesive parts in test 2 in boiling water and boil for 4 hours. Put them into a 63±3℃ forced air drying oven while they are still hot. After drying for 20 hours, continue to boil them in boiling water for 4 hours. Then soak them in cold water below 30℃ for 1 hour. Then perform shear test according to GB / T7124-2008 standard and DMA test.
[0131] Table 2 Specific test results
[0132]
[0133]
[0134] From the thermal performance test of Examples 1 to 10 and the comparative example, it can be seen that after the introduction of the polyimide block, the 5% thermal weight loss temperature of the modified epoxy resins of Examples 1 to 10 all exceeds 100°C, which is higher than the thermal weight loss temperature of the comparative example; the glass transition temperature of the modified epoxy resins of Examples 1 to 10 all exceeds 60°C, which is higher than 63°C of the pure epoxy resin. This is due to the increase in the molecular weight of the introduced polyimide and the presence of the intramolecular imide ring and the intermolecular cross-linked imide bond in the system, which increases the hard segment content of the polyimide-polyurethane, hinders the movement of the molecular chain, causes the glass transition temperature of the hard segment part to move to the high temperature direction, and the glass transition temperature is significantly increased. The main chain of the polyimide molecule generally carries a benzene ring structure and an imide ring structure, resulting in a strong interaction force between its molecular chains and a close stacking of the molecular chains, thus having a higher melting point and melt viscosity.
[0135] From the mechanical property tests of Examples 1 to 10 and the comparative example, it can be seen that the bonding performance of the polyimide-polyurethane block copolymer modified epoxy resin has been correspondingly improved. The shear strength, peel strength, impact strength, and complex viscosity of Examples 1 to 10 are higher than those of the epoxy resin in the comparative example. This is because the polyurethane and the epoxy resin form a co-continuous phase or a particle dispersed phase, which improves the toughness of the epoxy resin.
[0136] From the shear strength and glass transition temperature under wet heat and water boiling conditions, it can be seen that the shear strength and glass transition temperature of the modified epoxy resin are higher than those of pure epoxy resin. This is because the introduced imide group is a rigid structure and will not expand and deform under water boiling conditions; the polyurethane segment fills the gaps in the system, and water molecules are not easy to penetrate, so that the modified epoxy resin can maintain good bonding properties under wet heat and water boiling conditions.
[0137] Figure 1 This is the FTIR spectrum of the polyimide-blocked polyurethane prepared in step 4 of Example 1. As can be seen from the figure, 1723cm -1 ~1768cm -1 and 1656cm -1 ~1678cm -1 The characteristic peaks of carbamate and amide groups are at 3200cm -1 ~3500cm -1 The stretching vibration peak of -OH in -COOH disappears at 1777cm -1 ~1789cm -1 and 1713cm -1 ~1721cm -1 The characteristic peaks of imide indicate that -COOH and NH-CO were successfully imidized to synthesize PI-PU block copolymer. The synthesis of polyimide was confirmed by infrared spectrum.
Claims
1. A polyimide-polyurethane copolymer modified epoxy resin adhesive, characterized in that The invention is prepared from polyamic acid prepolymer, polyurethane prepolymer and epoxy resin. Specifically, polyamic acid prepolymer is added to polyurethane prepolymer for copolymerization to obtain polyamic acid segmented polyurethane prepolymer, the polyamic acid segmented polyurethane prepolymer is thermally imidized to obtain polyimide segmented polyurethane, and finally the polyimide segmented polyurethane is added to epoxy resin for physical crosslinking; the molar ratio of the polyurethane prepolymer to the polyamic acid prepolymer is (2.01-3):1; the mass ratio of the polyimide segmented polyurethane to the epoxy resin is (0.1-0.4):1; The polyamic acid prepolymer is synthesized from aromatic diamine and aromatic dianhydride; the aromatic diamine is m-phenylenediamine; the aromatic dianhydride is 3,3',4,4'-biphenyltetracarboxylic dianhydride, 4,4'-(hexafluoroisopropylene) diphthalic anhydride, 4,4'-biphenyl ether dianhydride or 3,3',4,4'-dibenzophenone tetracarboxylic dianhydride; The polyurethane prepolymer is synthesized from dehydrated polyol and dehydrated isocyanate; the dehydrated isocyanate is toluene-2,4-diisocyanate; the dehydrated polyol is polybutylene glycol; The general structural formula of the polyimide-blocked polyurethane is: Where n = 5 to 7; The R1 is -, The R2 is Wherein m=5~13.
2. The epoxy resin adhesive modified by polyimide-polyurethane copolymer according to claim 1, characterized in that The molar ratio of the aromatic diamine to the aromatic dianhydride is (1.01-2):
1.
3. The epoxy resin adhesive modified by polyimide-polyurethane copolymer according to claim 1, characterized in that The molar ratio of the dehydrated isocyanate to the dehydrated polyol is (1.01-3):
1.
4. The epoxy resin adhesive modified by polyimide-polyurethane copolymer according to claim 1, characterized in that The epoxy resin is E-51 epoxy resin; the molecular weight of the polybutylene glycol is 1000 g / mol to 3000 g / mol.
5. The method for preparing a polyimide-polyurethane copolymer modified epoxy resin adhesive according to claim 1, characterized in that It is carried out in the following steps:
1. Preparation of polyamic acid prepolymer: Weigh aromatic diamine, aromatic dianhydride and organic solvent in proportion, add aromatic diamine to organic solvent and stir to dissolve at room temperature, then add aromatic dianhydride and stir to dissolve at room temperature, then react for 1h to 2h at 20°C to 40°C, add deionized water under high-speed stirring after the reaction, stop stirring when the system becomes a milky white suspension, filter and wash, and finally dry to obtain a polyamic acid prepolymer; 2. Preparation of polyurethane prepolymer: Dehydrating the isocyanate and the polyol respectively, then weighing the dehydrated polyol and the dehydrated isocyanate in proportion, and then dripping the dehydrated isocyanate into the dehydrated polyol under a nitrogen atmosphere at a temperature of 60° C. to 80° C. for reaction for 2 h to 3 h to obtain a polyurethane prepolymer; 3. Preparation of polyurethane prepolymer with polyamic acid block: Under the conditions of nitrogen atmosphere and temperature of 60° C. to 80° C., adding polyamic acid prepolymer to polyurethane prepolymer for reaction for 0.5 h to 1 h to obtain polyamic acid-blocked polyurethane prepolymer; The molar ratio of the polyurethane prepolymer to the polyamic acid prepolymer is (2.01-3):1; 4. Thermal imidization: In a nitrogen atmosphere, the polyurethane prepolymer with polyamic acid blocks is thermally imidized to obtain a polyurethane with polyimide blocks; 5. Blending of polyimide-blocked polyurethane and epoxy resin: Under the conditions of nitrogen atmosphere and temperature of 60°C to 80°C, adding polyimide-blocked polyurethane to epoxy resin for reaction for 1h to 3h to obtain polyimide-polyurethane copolymer-modified epoxy resin adhesive; The mass ratio of the polyurethane of the polyimide block to the epoxy resin is (0.1-0.4):
1.
6. The method for preparing a polyimide-polyurethane copolymer modified epoxy resin adhesive according to claim 5, characterized in that The organic solvent described in step 1 is N,N-dimethylacetamide; the mass ratio of the total mass of the aromatic diamine and aromatic dianhydride described in step 1 to the organic solvent is 1:(2-5).
7. The method for preparing a polyimide-polyurethane copolymer modified epoxy resin adhesive according to claim 5, characterized in that In step 1, at room temperature and a stirring speed of 200 r / min to 400 r / min, an aromatic diamine is added to an organic solvent and stirred to dissolve, then at room temperature, a stirring speed of 200 r / min to 400 r / min and an addition speed of 1 mL / min to 2 mL / min, an aromatic dianhydride is added and stirred to dissolve, and then at a temperature of 20° C. to 40° C. and a stirring speed of 400 r / min to 600 r / min, the reaction is carried out for 1 h to 2 h to obtain a reaction system, and after the reaction, deionized water is added to the reaction system at a stirring speed of 1000 r / min to 1200 r / min and an addition speed of 3 mL / min to 5 mL / min, stirring is stopped when the system becomes a milky white suspension, and then suction filtration is performed to obtain a filter cake, the filter cake is washed 2 to 4 times with acetone and deionized water, and finally dried; the volume ratio of the reaction system to deionized water is 1:(1.5 to 2.5).
8. The method for preparing a polyimide-polyurethane copolymer modified epoxy resin adhesive according to claim 5, characterized in that The dehydration in step 2 is specifically carried out at a temperature of 100° C. to 110° C. for 2 h to 3 h.
9. The method for preparing a polyimide-polyurethane copolymer modified epoxy resin adhesive according to claim 5, characterized in that In step 2, under the conditions of nitrogen atmosphere, temperature of 60°C to 80°C, stirring speed of 400r / min to 600r / min and dropping speed of 0.25mL / min to 1mL / min, the dehydrated isocyanate is dropped into the dehydrated polyol to react for 2h to 3h.
10. The method for preparing a polyimide-polyurethane copolymer modified epoxy resin adhesive according to claim 5, characterized in that The thermal imidization described in step 4 is specifically carried out under a nitrogen atmosphere, first at a temperature of 60°C to 65°C for 1h to 1.5h, then at a temperature of 70°C to 80°C for 1h to 1.5h, then at a temperature of 85°C to 90°C for 1h to 1.5h, then at a temperature of 95°C to 100°C for 1h to 1.5h, and finally at a temperature of 110°C to 120°C for 1h to 1.5h.
Citation Information
Patent Citations
Special heat-resisting epoxy resin adhesive for stone material
CN106753123A
Adhesive composition containing a dimer diol copolymer polyimide urethane resin
CN113286835A
Solvent for resin synthesis and method for producing synthetic resin using same
CN116075537A
Resin for ship composite material and preparation method thereof
CN116144139A
Cited By
High-strength yellow fluorescent polyurethane elastomer and preparation method thereof
CN120271785A